Bistable self-assembly in homogeneous colloidal systems for flexible modular architectures. Issue 10 (1st February 2016) - Steinbach, G.; Nissen, D.; Albrecht, M.; Novak, E. V.; Sánchez, P. A.; Kantorovich, S. S.; Gemming, S.; Erbe, A.
Abstract : Magnetic Janus particles with anisotropic magnetization distribution provide bistable self-assembly patterns, allowing for the growth of complex, flexible networks. Abstract : This paper presents a homogeneous system of magnetic colloidal particles that self-assembles via two structural patterns of different symmetry. Based on a qualitative comparison between a real magnetic particles system, analytical calculations and molecular dynamics simulations, it is shown that bistability can be achieved by a proper tailoring of an anisotropic magnetization distribution inside the particles. The presented bistability opens new possibilities to form two-dimensionally extended and flexible structures where the connectivity between the particles can be changed in vivo .